2012
DOI: 10.1002/adsc.201200175
|View full text |Cite
|
Sign up to set email alerts
|

1,10‐Phenanthroline‐Catalyzed Tandem Reaction of 2‐Iodoanilines with Isothiocyanates in Water

Abstract: The 1,10-phenanthroline-catalyzed tandem reaction of 2-iodoaniline with isothiocyanate in water is described, which provides an environmentally benign, efficient and simple route for the preparation of 2-aminobenzothiazoles. The present tandem process shows broad substrate scope in the absence of transition metals and phase-transfer catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 41 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…2-Aminobenzothiazoles and thiazoles are versatile synthetic intermediates and are widely used in the synthesis of various biologically active compounds. In particular, N -alkylated thiazoles and benzothiazoles exhibit different pharmacological and physiological activities. , As a result, much attention has been paid to the synthesis of these compounds. By considering the importance of 2-aminobenzothiazole derivatives, we investigated herein the N -alkylation of 2-aminobenzothiazoles, and the method has been extended to other heteroaromatic amines including pyridine, pyrimidine, and pyrazines with various alcohols. Under these conditions, we found the N 1 ,C 5 -dialkylation of 4-phenyl-2-aminothiazoles, and there were no reports found for this type of transformation.…”
mentioning
confidence: 99%
“…2-Aminobenzothiazoles and thiazoles are versatile synthetic intermediates and are widely used in the synthesis of various biologically active compounds. In particular, N -alkylated thiazoles and benzothiazoles exhibit different pharmacological and physiological activities. , As a result, much attention has been paid to the synthesis of these compounds. By considering the importance of 2-aminobenzothiazole derivatives, we investigated herein the N -alkylation of 2-aminobenzothiazoles, and the method has been extended to other heteroaromatic amines including pyridine, pyrimidine, and pyrazines with various alcohols. Under these conditions, we found the N 1 ,C 5 -dialkylation of 4-phenyl-2-aminothiazoles, and there were no reports found for this type of transformation.…”
mentioning
confidence: 99%
“…Although various synthetic methods have been developed for their synthesis, the cross‐coupling of 2‐haloarylamines with isothiocyanates has been recognized as a powerful and efficient route [9] . On the other hand, several types of catalysts, including transition metal catalysts, [11–15] organic catalysts, [16] metal organic framework (MOFs), [17] nano metal particles [18] and porous aromatic framework materials (PAFs), [19] have been successfully employed to promote such cross‐coupling reaction. Also, recent studies revealed that the 1,10‐phenanthroline (Phen) played a central role in the process of formation of 2‐aminobenzothiazoles [14–16,19,20] …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, several types of catalysts, including transition metal catalysts, [11–15] organic catalysts, [16] metal organic framework (MOFs), [17] nano metal particles [18] and porous aromatic framework materials (PAFs), [19] have been successfully employed to promote such cross‐coupling reaction. Also, recent studies revealed that the 1,10‐phenanthroline (Phen) played a central role in the process of formation of 2‐aminobenzothiazoles [14–16,19,20] …”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ding’s group has realized the synthesis of 2‐imino‐1,3‐oxathioles in water with 37% yield in the presence of an inexpensive base, and in this reaction, high temperature and N 2 protection were necessary 9a. We have developed a transition metal‐free synthesis of 2‐aminobenzothiazoles from 2‐iodoanilines and isothiocyanates using Phen as catalyst in water 9b. Cai et al.…”
Section: Introductionmentioning
confidence: 99%